2018
DOI: 10.1016/j.ihj.2018.10.395
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing prehospital delay in patients presenting with ST-elevation myocardial infarction and the impact of prehospital electrocardiogram

Abstract: BackgroundIn ST-elevation myocardial infarction (STEMI), prehospital delay is a significant factor, decreasing likelihood of revascularization and increasing mortality. Prehospital delays are substantive in Indian patients with STEMI. Our study aimed to investigate factors associated with prehospital delay in patients with STEMI.MethodsA multicentric prospective analysis was conducted at five major cardiac care referral centers in Punjab including a tertiary care teaching hospital over a period of 1 year from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
48
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 23 publications
(21 reference statements)
11
48
2
1
Order By: Relevance
“…Older age had also been noted to be risk factor of pre-hospital delay (16,18,22) , and this may be due to limited resources and problem with transportation. There was no signi cant difference in pre-hospital delay between both the genders in our study, and this was consistent with most other studies from both developed and developing countries (10,16,(23)(24)(25). However, some studies identi ed female gender as one of the predictors of pre-hospital delay (12,26).…”
Section: Discussionsupporting
confidence: 92%
“…Older age had also been noted to be risk factor of pre-hospital delay (16,18,22) , and this may be due to limited resources and problem with transportation. There was no signi cant difference in pre-hospital delay between both the genders in our study, and this was consistent with most other studies from both developed and developing countries (10,16,(23)(24)(25). However, some studies identi ed female gender as one of the predictors of pre-hospital delay (12,26).…”
Section: Discussionsupporting
confidence: 92%
“…Similar finding is present in a previous studies where patients claimed longer distance of primary care center for late presentation (22,24,28). However the mode of transport (ambulance or general vehicle) was not associated with delayed hospital presentation in our study, though a study showed that patients who used private ambulance had shorter delay compared to those who used public ambulance or other transport (26).…”
Section: Pre-hospital Delaysupporting
confidence: 91%
“…Older age is a widely reported risk factor of prolong pre-hospital delay (16,18,21). No significant sex difference were found in case of pre-hospital delay in this study, which is consistent with other studies from both developed and developing countries including the Bangladeshi one (10,16,(22)(23)(24). However, some other studies identified female sex as significant predictors of prolonged pre-hospital delay (12,25).…”
Section: Pre-hospital Delaysupporting
confidence: 89%
See 2 more Smart Citations